Effect of Organic Amendment and Cultural Practice on Large Patch Occurrence and Soil Microbial Community. Issue 4 (25th May 2017) - Pan, Xiaowei; Richardson, Michael D.; Deng, Shiping; Kremer, Robert J.; English, James T.; Mihail, Jeanne D.; Sams, Carl E.; Scharf, Peter C.; Veum, Kristen S.; Xiong, Xi
Abstract : Organic amendments often stimulate soil microorganisms that result in suppression of soilborne pathogens. However, little information is available about the influences of organic amendments and cultural practices on suppression of Rhizoctonia solani Kühn, which causes large patch on zoysiagrass ( Zoysia japonica Steud.). The objective of this study was to evaluate the effect of organic amendments and cultural practices of aerification + topdressing or topdressing on large patch and on changes in soil microbial community composition. A 2‐yr field experiment was conducted on a zoysiagrass fairway in Columbia, MO. Organic amendments included an animal waste‐based product (AW, chicken manure), a sewage‐based organic N fertilizer (Milorganite), and a plant byproduct (oriental mustard [ Brassica juncea (L.) Czern.] seed meal), in addition to a synthetic nitrogen fertilizer (UMAXX), a synthetic fungicide (SF, azoxystrobin), and a nontreated control (NC). The amendments were applied as topdressing either after aerification or as topdressing alone twice per year for 2 yr. Area under disease progress curve (AUDPC) indicated that disease severity in AW‐ and SF‐treated plots was reduced by 49 and 86%, respectively, compared with NC. Amendments applied resulted in a shift of soil bacterial community as measured by the Gram‐positive to Gram‐negative bacteria ratio (G+/G−), a trend similar to that of the AUDPC. Aerification + topdressing resulted in lower fungi, fungi to bacteria ratio, and stress indicators than topdressing, suggesting that aerification + topdressing stressed fungi but stimulated bacteria. Addition of AW led to significant R. solani suppression, which may be associated with the reduced G+/G− ratio.